From Genes to Transcripts, a Tightly Regulated Journey in Plasmodium - Hollin, Thomas; Le Roch, Karine G. (Frontiers in Cellular and Infection Microbiology, 2020)
Over the past decade, we have witnessed significant progresses in understanding gene regulation in Apicomplexa including the human malaria parasite, Plasmodium falciparum. This parasite possesses the ability to convert in multiple stages in various hosts, cell types, and environments. Recent findings indicate that P. falciparum is talented at using efficient and complementary molecular mechanisms to ensure a tight control of gene expression at each stage of its life cycle. Here, we review the current understanding on the contribution of the epigenome, atypical transcription factors, and chromatin organization to regulate stage conversion in P. falciparum. The adjustment of these regulatory mechanisms occurring during the progression of the life cycle will be extensively discussed.